Addiction and Other Reasons Adolescent Smokers Give to Justify Smoking. (15th October 2015) - Borderías, Luis; Duarte, Rosa; Escario, José Julián; Molina, José Alberto
Abstract : Background: The primary purpose of this paper is to examine youth addiction and other justifications for adolescent smoking, and how they affect the level of consumption. Methods: Data from the Spanish 'State Survey on Drug Use among High School Students' aged between 14 and 18 years old were used in this paper. To account for the nature of the cigarette consumption data, several count data models were estimated in order to select the one that best fits adolescent smoking consumption. Results: Most adolescent smokers smoke because it relaxes them, and about a quarter of them recognize that they are addicted. Moreover, the latter group smoke 44% more cigarettes than the rest (IRR = 1.444), revealing the strong addictive nature of tobacco, even at early ages. Moreover, parents' smoking increases the probability of smoking and has an impact on the level of consumption. Conclusions: The implications of these findings offer insight for parents, researchers, educators, and cessation interventionists, as awareness of self-reported and other predictors held by smoking youth creates a vantage point to facilitate changes in smoking behavior.